Health Communication Literacy Counseling through Health Halo Effect Education in the Formation of Food Product Image in Senior High School Students - Surianto Surianto; Ahya Radiatul Kamila; Very Budiyanto; Alaniah Nisrina; Agung Stefanus Kembau (Asian Journal of Community Services, 2026)
This community engagement program aimed to improve high school students’ awareness of the Halo Effect in marketing communication and encourage critical evaluation of health-related product claims. Before the intervention, 100% of participants perceived the product as healthy milk, while 65% associated it with high calcium content, indicating a strong spontaneous health perception. The intervention introduced the Halo Effect and demonstrated how visual and verbal packaging cues may influence consumer judgments. Following the intervention, participants’ responses indicated greater attention to nutritional information, ingredient composition, and product claims when evaluating product healthfulness. Future programs should incorporate structured evaluation instruments to enable quantitative assessment of changes in health communication literacy.